Sulphaphenazole, streptomycin and sulphaphenazole combination, trimethoprim, and erythromycin in the treatment of chancroid. Issue 2 (April 1990) - Kumar, B; Sharma, V K; Bakaya, V
Abstract : One hundred and thirty six patients with chancroid were treated with four different treatment regimens; (A) Sulphaphenazole 1 g 12 hourly by mouth x 10 days (B) Inj streptomycin 1 g intramuscularly daily with sulphaphenazole 1 g 12 hourly orally x 10 days; (C) trimethoprim 200 mg 12 hourly by mouth x 7-10 days, and (D) erythromycin 500 mg 6 hourly orally x 7-10 days. Cure rates of 9% with sulphaphenazole alone, 48% with streptomycin and sulphaphenazole combination, 93% with trimethoprim and 100% with erythromycin were obtained. Sulphaphenazole alone or in combination with streptomycin were thus inferior in the treatment of chancroid. There is need for modification of treatment regimens recommended for chancroid in the textbooks of dermatology and venereology. Trimethoprim can be recommended as first line of treatment for chancroid in developing countries like India where resistance to trimethoprim is uncommon and erythromycin is suggested as a second line of therapy because by that time syphilis can be easily ruled out.